2012
DOI: 10.1016/j.quascirev.2011.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Holocene distribution of woody taxa at the westernmost limit of the Circumboreal/Mediterranean boundary: Evidence from wood remains

Abstract: Macrofossils and megafossils of different genera, which were found in twelve localities in the mountains of northwest Iberia, provide spatially precise evidence of their distribution in the region during the Holocene. Macrofossils were recovered from mires, eroded peat bogs and lakes, identified by their wood anatomy and dated using radiocarbon methods. Conifers (Pinus), deciduous trees (Betula, Salix, Quercus) and shrubs (Erica, Fabaceae) were identified. The findings of Pinus gr. sylvestris/nigra have specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 61 publications
(86 reference statements)
0
10
0
4
Order By: Relevance
“…The reasons for this phenomenon are probably climatic. The increased precipitation and temperature in the early middle Holocene, as detected in lake, bog, marine sediment and speleothem records in the northern Iberian Peninsula (Santos et al 2000;Roucoux et al 2001;Moreno et al 2011;Stoll et al 2013), which resulted in tree recolonization, caused an early decline of pine forests across Rubiales et al (2008Rubiales et al ( , 2011Rubiales et al ( , 2012. Deciduous taxa, especially Quercus, Corylus and sometimes Betula, in this temperate and humid climate had certain advantages that allowed them to compete successfully against coniferous formations, which survived in other areas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The reasons for this phenomenon are probably climatic. The increased precipitation and temperature in the early middle Holocene, as detected in lake, bog, marine sediment and speleothem records in the northern Iberian Peninsula (Santos et al 2000;Roucoux et al 2001;Moreno et al 2011;Stoll et al 2013), which resulted in tree recolonization, caused an early decline of pine forests across Rubiales et al (2008Rubiales et al ( , 2011Rubiales et al ( , 2012. Deciduous taxa, especially Quercus, Corylus and sometimes Betula, in this temperate and humid climate had certain advantages that allowed them to compete successfully against coniferous formations, which survived in other areas.…”
Section: Discussionmentioning
confidence: 99%
“…In this area, the 19th‐century authors Willkomm & Lange (), following the works of Planelles () and Olazabal (), suggested the nature of relict Scots pine forests in the Cantabrian Mountains (Rubiales et al . , ). Similarly, Catón‐Santaren & Uribe‐Etxebarria (), Ruiz‐Urrestarazu () and Aseginolaza et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…La presencia de estos bosques en zonas elevadas de la Cordillera Cantábrica es un tema largamente discutido. Desde el Tardiglaciar y los inicios del Holoceno, la mayoría de los estudios paleobotánicos del norte de la Península Ibérica indican que los pinos jugaron un papel importante en la recuperación postglacial de los bosques (Menéndez Amor y Florschütz, 1963;Hannon, 1985;Watts, 1986;Muñoz Sobrino et al, 2007, López Merino, 2009Rubiales et al, 2010Rubiales et al, , 2012. En el caso concreto de la Cordillera Cantábrica, son numerosísimas las evidencias palinológicas que demuestran la importancia de los pinares durante el Holoceno inicial y medio (Menéndez Amor y Florschütz, 1963;Menéndez Amor, 1968;Peñalba, 1989;Belet, 1993;Allen et al, 1996;Muñoz Sobrino et al, 1996, 1997Santos et al, 2000;Iriarte et al, 2001Iriarte et al, , 2003García Rovés et al, 2001;García Rovés, 2007;Moreno et al, 2011;Pérez Díaz et al, 2016), en las mismas fechas que en el registro paleoambiental de Sotombo.…”
Section: Bosques Caducifolios Y Pinares En La Cordillera Cantábrica Cunclassified